Achieving the Most Effective Hanging Points at the Lower End of the Face for Thread Lifting: Quantitative Measurement of Tissue Resistance in Different Facial Layers. Issue 7 (15th July 2021) - Rungsawang, Chalermquan; Tansatit, Tanvaa; Fasunloye, Liz Kenny; Uruwan, Sukanya
Abstract : Summary: The thread lift procedure is a minimally invasive alternative to facelift surgery. The hanging point, which the terminal end of the thread is hooked into, is an important component. If it is loose and cannot stabilize the passage when the inserted thread is pulled, the lifting effect will fail. Therefore, the aim of this study was to elucidate the ability of the tissue to support the thread attachment in the different facial layers while performing this procedure. Twenty hemi-faces of 10 soft cadavers, which were divided into 45 blocks, were used to measure the tissue resistance in the midface area. The resistance of the soft tissue in the four facial layers in each block was measured while a 22G cannula connected with a force gauge was passed through it. The results showed that the tissue resistance in the sub-SMAS was higher than the SMAS and subcutaneous layers in the blocks located in the nasolabial and perioral regions. This was also significantly greater than the resistance in the subcutaneous layer in the three medial blocks below the oral commissure ( P < 0.05). However, the low resistance of the sub-SMAS was found in the blocks located in the buccal and lower parotidomasseteric regions. Thus, it was preferable that the hanging point was based in the deep plane (sub-SMAS and SMAS layers) of the nasolabial, perioral, and upper parotidomasseteric regions. Moreover, the sub-SMAS layer within the buccal and lower parotidomasseteric regions should be avoided due to the loose attachment in the buccal capsule and subplatysmal fat.